LEGAL ISSUES REPRESENTATION IN COURT ON ECONOMIC CASES (American Journal of Pedagogical and Educational Research, 2024)
This article discusses the issues of participation of representatives in the economic process, formalization of the powers of the representative, the powers of the persons participating in the case and their representatives, as well as the rights, duties and responsibilities of representatives.